2023
DOI: 10.1002/art.42418
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Latent Epitope Causing Differential Binding of Antineutrophil Cytoplasmic Antibodies to Proteinase 3

Abstract: Objective Proteinase 3 (PR3) is the major antigen for antineutrophil cytoplasmic antibodies (ANCAs) in the systemic autoimmune vasculitis, granulomatosis with polyangiitis (GPA). PR3‐targeting ANCAs (PR3‐ANCAs) recognize different epitopes on PR3. This study was undertaken to study the effect of mutations on PR3 antigenicity. Methods The recombinant PR3 variants, iPR3 (clinically used to detect PR3‐ANCAs) and iHm5 (containing 3 point mutations in epitopes 1 and 5 generated for epitope mapping studies) immunoas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…We previously showed that remote mutations and engagement of distal epitopes by an anti-PR3 monoclonal antibody can increase the local mobility and expose latent PR3 epitopes, leading to conformational adaptation facilitating or necessary for antibody binding 16 17. This type of epitope activation—achieved in vitro by remote mutations, or in vivo either by polymorphisms or by binding of another autoantibody or protein ligand—may be an important contributor of PR3-AAV pathogenesis 16 17. Our observation that homozygosity for the PRTN3-Val 119 Ile polymorphism is associated with a different risk for severe relapses is consistent with the hypothesis that the two different PR3 antigen variants may interact differently with pathogenic PR3-ANCA.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We previously showed that remote mutations and engagement of distal epitopes by an anti-PR3 monoclonal antibody can increase the local mobility and expose latent PR3 epitopes, leading to conformational adaptation facilitating or necessary for antibody binding 16 17. This type of epitope activation—achieved in vitro by remote mutations, or in vivo either by polymorphisms or by binding of another autoantibody or protein ligand—may be an important contributor of PR3-AAV pathogenesis 16 17. Our observation that homozygosity for the PRTN3-Val 119 Ile polymorphism is associated with a different risk for severe relapses is consistent with the hypothesis that the two different PR3 antigen variants may interact differently with pathogenic PR3-ANCA.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, homozygosity for this polymorphism, which is the only one resulting in a change of the amino acid sequence of PR3, may represent an additional identifiable risk factor for severe relapse. Moreover, our data suggest that the quantity of PR3 expressed in patients with AAV compared with healthy controls and conformational changes of the autoantigen may modulate its interactions with pathogenic PR3-ANCA promoting disease activity 17 18. Further studies are necessary to validate and better understand the association of this observation with the risk of severe relapse and its possible molecular mechanisms.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations